Work Analysis of An Assembly Operation Using Therbligs - Anh Le (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to analyze an assembly operation using work analysis technique. The LED bulb assembly operation is studied because it is labor-intensive manufacturing. This operation requires highly repetitive motions of two hands of worker. Therbligs represent motions when worker assemble the parts. Therefore, Therbligs are used to analyze the movements of worker in this study. The results shown that the ineffective motions such as search, select and hold can be minimized or eliminated by using fixture and rearranging workstation.